New aromataze inhibitor (letrozol) in treatment of advanced breast cancer - Skowronek, Janusz (Contemporary Oncology/Współczesna Onkologia, 1999)
Patients with advanced breast cancer constitute 4 to 20% of patients with breast cancer. Results of treatment are still disappointing. Drugs like aromatase inhibitors decrease biosynthesis of estrogens which stymulate tumor growth, they prove to be especially effecive in treatment of advanced breast cancer in postmenopausal women with hormonal-dependent breast cancer. In this paper the new aromatase inhibitor (letrozol) is described. Indication for treatment, contrindications and adverse experiences are presented. Efficacy of treatment of advanced breast cancer patients with letrozol and others aromatase inhibitors is compared.